Beringia and the global dispersal of modern humans. Issue 2 (4th March 2016) - Hoffecker, John F.; Elias, Scott A.; O'Rourke, Dennis H.; Scott, G. Richard; Bigelow, Nancy H.
Abstract : Until recently, the settlement of the Americas seemed largely divorced from the out‐of‐Africa dispersal of anatomically modern humans, which began at least 50, 000 years ago. Native Americans were thought to represent a small subset of the Eurasian population that migrated to the Western Hemisphere less than 15, 000 years ago. Archeological discoveries since 2000 reveal, however, that Homo sapiens occupied the high‐latitude region between Northeast Asia and northwest North America (that is, Beringia) before 30, 000 years ago and the Last Glacial Maximum (LGM). The settlement of Beringia now appears to have been part of modern human dispersal in northern Eurasia. A 2007 model, the Beringian Standstill Hypothesis, which is based on analysis of mitochondrial DNA (mtDNA) in living people, derives Native Americans from a population that occupied Beringia during the LGM. The model suggests a parallel between ancestral Native Americans and modern human populations that retreated to refugia in other parts of the world during the arid LGM. It is supported by evidence of comparatively mild climates and rich biota in south‐central Beringia at this time (30, 000‐15, 000 years ago). These and other developments suggest that the settlement of the Americas may be integrated with the global dispersal of modern humans.